2006
DOI: 10.1002/bdrb.20091
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity studies in Crl:CD (SD) rats following inhalation exposure to trichloroethylene and perchloroethylene

Abstract: The potential for trichloroethylene (TCE) and perchloroethylene (PERC) to induce developmental toxicity was investigated in Crl:CD (SD) rats whole-body exposed to target concentrations of 0, 50, 150 or 600 ppm TCE or 0, 75, 250 or 600 ppm PERC for six hours/day, seven days/week on gestation day (GD) 6-20 and 6-19, respectively. Actual chamber concentrations were essentially identical to target with the exception of the low PERC exposure level, which was 65 ppm. The highest exposure levels exceeded the limit co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 23 publications
(37 reference statements)
2
48
0
3
Order By: Relevance
“…Some studies identified significant treatment-related increases in the overall incidence of cardiac anomalies at environmentally relevant exposure levels (e.g., Johnson et al 2003, 2005), whereas others reported no excess cardiac abnormalities at much higher dose levels (e.g., Carney et al 2006; Fisher et al 2001). Several methodological factors may contribute to differences across study outcomes, such as the route of administration, test substance purity, test species or strain, timing of dosing or fetal evaluation, procedures used in dissecting and examining fetal hearts, statistical approaches applied to data evaluation, and generally uncharacterized interlaboratory variation.…”
Section: Noncancer Toxicitymentioning
confidence: 99%
“…Some studies identified significant treatment-related increases in the overall incidence of cardiac anomalies at environmentally relevant exposure levels (e.g., Johnson et al 2003, 2005), whereas others reported no excess cardiac abnormalities at much higher dose levels (e.g., Carney et al 2006; Fisher et al 2001). Several methodological factors may contribute to differences across study outcomes, such as the route of administration, test substance purity, test species or strain, timing of dosing or fetal evaluation, procedures used in dissecting and examining fetal hearts, statistical approaches applied to data evaluation, and generally uncharacterized interlaboratory variation.…”
Section: Noncancer Toxicitymentioning
confidence: 99%
“…In a study designed to examine the effects of perc on fertility, female rats were exposed to inhaled perc for 2 hours/day, 5 days/week for 2 weeks and the oocytes extracted; the percentage of fertilized oocytes in vitro was reduced in perc-treated females as compared with controls (Berger and Horner, 2003). However, this study found no effect from exposure in drinking water, and other studies in rats also found no change in fertility (Carney et al, 2006;Tinston, 1994). An earlier study reported an increase in fertility of female rats exposed to perc (Carpenter, 1937).…”
Section: Preconception Outcomesmentioning
confidence: 65%
“…In experimental animals, exposure to perc caused decreased birth weight (Tinston, 1994) and decreased fetal body weight in some studies of rats (Carney et al, 2006;Szakmáry et al, 1997) and mice (Schwetz et al, 1975). However, no effect on birth weight was found in other studies of mice (Szakmáry et al, 1997), rats (Hardin et al, 1981;Schwetz et al, 1975), and rabbits (Hardin et al, 1981;Szakmáry et al, 1997).…”
Section: Prenatal and Birth Outcomesmentioning
confidence: 98%
See 2 more Smart Citations